Physicochemical characterization and consumer preference of rice (Oryza sativa) varieties grown in Costa Rica - Guadamuz-Mayorga, Carolina; Cubero-Castillo, Elba; Azofeifa, Alvaro; Montero, Maria Laura; Araya-Morice, Adriana (Archivos Latinoamericanos de Nutrición (ALAN), 2022)
Introduction: Rice is a staple food in Costa Rica representing almost 24 % of the total calorie intake in the diet. Consumers have become more quality conscious about the rice consumed, so producers need to focus on the quality of rice along with production. Objective: The aim of this study was to investigate the physicochemical profile and consumer preference of five Costa Rican rice varieties: Palmar 18, Basmatico, Chin Chin, INTA-Miravalles, and CR- 5272. Materials and methods: Proximate analysis, amylose, and mineral content were performed in the raw grain. Two different sessions were performed (n=120 each) to evaluate consumer preference measurements using the John Brown R-Index (RJB) index. The first sensory panel selected the best cooking preparation and the second, the preferred rice variety. Instrumental color measurements (L*, C*, hº, DE) were applied to the cooked rice varieties (76-96ºC for 38 min). Results: Regarding the physicochemical characterization, INTAMiravalles showed the highest protein content (8.2%), while Basmatico and Chin Chin, the lowest. Four varieties presented high amylose content (AC) and INTA-Miravalles reported an intermediate AC. The mineral content varied among varieties. INTA-Miravalles showed the highest N, followed by Palmar 18. The cooking preparation from the regulatory agency was preferred by consumers. The consumers’ preference of the varieties ranked from high to low: Basmatico>Chin Chin=CR5772>Palmar 18=INTA-Miravalles. Conclusions: This study suggests that consumer preference for cooked rice was influenced by physicochemical characteristics such as protein, AC, mineral content, and aromatic attributes. Consumer acceptance is an important factor to consider when new varieties are developed. The water-to-rice ratio during cooking played an important role in cooked rice sensory quality. Introducción: el arroz es un alimento básico de consumo en Costa Rica que representa casi el 24% de la ingesta total de calorías en la dieta. Los consumidores se han vuelto más conscientes de la calidad del arroz que consumen, por lo que los productores deben enfocar esfuerzos en la calidad y producción del arroz. Objetivo: El objetivo de este estudio fue investigar el perfil fisicoquímico y la preferencia del consumidor de cinco variedades de arroz de Costa Rica: Palmar 18, Basmatico, Chin Chin, INTA-Miravalles y CR-5272. Materiales y métodos: Se realizó el análisis proximal, contenido de amilosa (CA) y de minerales en el grano crudo y color instrumental en el arroz cocido. Se realizaron dos mediciones de preferencia de los consumidores (n=120) utilizando el índice R de James Brown (RJB). En la primera se seleccionó el mejor método de preparación y en la segunda, la variedad de arroz preferido. El color instrumental (L*, C*, hº, DE) se midió a las variedades de arroz cocinado (76-96ºC por 38 min). Resultados: Miravalles mostró el mayor contenido en proteínas (8,2%), mientras que Basmatico y Chin Chin, el menor. Cuatro variedades presentaron un alto CA y el INTAMiravalles reportó un CA intermedio. El contenido mineral varió entre las variedades. INTA-Miravalles mostró el mayor contenido de nitrógeno, seguido de Palmar 18. El método de cocción del ente regulador fue el preferido por los consumidores. La preferencia de los consumidores por las variedades de mayor a menor fue: Basmatico > Chin Chin = CR5772 > Palmar 18 = INTA-Miravalles. Conclusiones: La preferencia de los consumidores por el arroz cocido se vio influenciada por características fisicoquímicas como proteína, CA, minerales y atributos aromáticos. La aceptación de los consumidores es un factor importante cuando se desarrollan nuevas variedades. La relación agua/ arroz durante la cocción desempeñó un papel importante en la calidad del arroz cocido.